2022
DOI: 10.1177/02698811221104065
|View full text |Cite
|
Sign up to set email alerts
|

Alprazolam-related deaths in Scotland, 2004–2020

Abstract: Background: The benzodiazepine drug alprazolam, a fast-acting tranquiliser, cannot be prescribed on the National Health Service in the United Kingdom. Illicit alprazolam supply and consumption have increased. Concern about increasing numbers of alprazolam-related fatalities started circulating in 2018. However, statistics on this issue are very limited. This study examined patterns in such mortality in Scotland. Methods: Statistics on deaths where alprazolam was mentioned in the ‘cause of death’ were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Similar to the United States and Canada, the combined use of opioids with benzodiazepines and related drug deaths are also highly prevalent in Scotland. Of all drug-related deaths in Scotland in 2021 ( n = 1330), drug analyses showed that in 93% of the victim's body more than one drug was detected, 84% involved opiates or opioids (such as heroin, morphine and methadone), only 3% involved amphetamines and 69% involved benzodiazepines [45 ▪ ,46] mostly diazepam (68% of all benzodiazepines) and/or etizolam (31% of all benzodiazepines) [47]. Nonfatal overdoses in Tayside (Scotland) between December 2017 and May 2019 in a sample of people attending addiction treatment service ( n = 557) showed that methadone (58%), benzodiazepines (50%) and heroin (44%) were the most commonly self-reported drugs, whereas opioids and benzodiazepines were the most often co-used drugs (49%) [48].…”
Section: Drd Following Simultaneous Use Of Opioids and Benzodiazepinesmentioning
confidence: 99%
“…Similar to the United States and Canada, the combined use of opioids with benzodiazepines and related drug deaths are also highly prevalent in Scotland. Of all drug-related deaths in Scotland in 2021 ( n = 1330), drug analyses showed that in 93% of the victim's body more than one drug was detected, 84% involved opiates or opioids (such as heroin, morphine and methadone), only 3% involved amphetamines and 69% involved benzodiazepines [45 ▪ ,46] mostly diazepam (68% of all benzodiazepines) and/or etizolam (31% of all benzodiazepines) [47]. Nonfatal overdoses in Tayside (Scotland) between December 2017 and May 2019 in a sample of people attending addiction treatment service ( n = 557) showed that methadone (58%), benzodiazepines (50%) and heroin (44%) were the most commonly self-reported drugs, whereas opioids and benzodiazepines were the most often co-used drugs (49%) [48].…”
Section: Drd Following Simultaneous Use Of Opioids and Benzodiazepinesmentioning
confidence: 99%
“…In Scotland, for example, deaths from BZDs, including diazepam and etizolam, increased from 26% in 2008 to 57% in 2022 of the total number of drug misuse deaths [ 5 , 6 ]. The implications of these BZD analogues’ DRDs, accidental or otherwise, are widely debated [ 7 , 8 ]. Often, BZD DRDs are related to the combined inhibitory effects of both BZDs on GABA A receptors, and other CNS depressants, such as opioids, on opioid receptors in respiratory control centres, thus facilitating respiratory depression when co-consumed, and potentially leading to deaths [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This process can be studied using self-administration (actual consumption) or hypothetical purchase tasks (simulated) and applying demand curve analysis to examine the intensity and elasticity of demand (53,54), which can also be conceptualized as amplitude and persistence of demand, respectively (55). Alprazolam is a rapid-onset BZD that is frequently misused (56)(57)(58)(59). Studies of rhesus monkeys have demonstrated that BZDs are self-administered, however, economic demand for BZDs is complexly related to a compound's selectivity and intrinsic efficacy at α1 subunit-containing GABA A receptors, as well as the animal's baseline history of self-administration (60)(61)(62)(63)(64).…”
Section: Introductionmentioning
confidence: 99%